Fast Synthesis of High Quality Biodiesel from ‘Waste Fish Oil’ by Single Step Transesterification - Sharma, Yogesh C.; Singh, Bhaskar; and et. al.; Madhu, Devarapaga (Green Wave Publishing of Canada, 2014)
A large volume of fish wastes is produced on a daily basis in the Indian sub-continent. This abundant waste source could serve as an economic feedstock for bioenergy generation. In the present study, oil extracted from discarded fish parts was used for high quality biodiesel production. More specifically, a single step transesterification of 'waste fish oil' with methanol using sodium methoxide (CH3ONa) as homogeneous catalyst under moderate operational conditions resulted in highly pure biodiesel of > 98% of fatty acid methyl ester (FAME) content. Characterization was performed by Fourier Transform-Nuclear Magnetic Resonance (FT-NMR).
Keywords: Biodiesel; Fourier Transform-Nuclear Magnetic Resonance (FT-NMR); Single step transesterification; Waste fish oil